The status of probiotics supplementation during pregnancy (Medical Journal of Indonesia, 2015)
Probiotics have been known for their use in medical field for quite a long time. Strong evidences are now available for the use of probiotics in clinical setting. One of the current issues on this topic is the use of probiotics in pregnancy. Recent studies showed that probiotics may be safe and beneficial for prenatal supplementation. In this review, we highlighted several proven use of probiotics supplementation in pregnant women. A few selected strains of probiotics showed promising outcome to prevent preterm labor and preeclampsia, and to reduce atopic eczema but not asthma and wheezing, in offspring of women who had prenatal probiotics supplementation. The mechanism of action responsible for this effect is closely related to the regulation of T cells, although the exact pathways are not defined yet.